2012
DOI: 10.1016/j.imbio.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in complement regulators and susceptibility to age-related macular degeneration

Abstract: ObjectivesAge-related macular degeneration (AMD) is the commonest cause of blindness in Western populations. Risk is influenced by age, genetic and environmental factors. Complement activation appears to be important in the pathogenesis and associations have been found between AMD and genetic variations in complement regulators such as complement factor H. We therefore investigated other complement regulators for association with AMD.MethodsWe carried out a case–control study to test for association between AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…57 CD46 is also a clinically "attractive" molecule because single nucleotide polymorphisms in the CD46 gene are either causative or contribute to hemolytic uremic syndrome, age-related macular degeneration, and possibly pre-eclampsia. [58][59][60] On resting CD4 + T cells, CD46 presence sustains (via signals that have not yet been identified) the expression of the interleukin (IL)-7 receptor (CD127). Incoming IL-7R signals in circulating T cells maintain basic glucose transporter 1 (GLUT1) surface expression, which, in turn, allows for glucose-mediated protein kinase B (AKT) activation and anti-apoptotic B cell lymphoma (BCL-2) expression, all such events being required for normal T cell survival in the periphery.…”
Section: The Complosome In T Cell Homeostasismentioning
confidence: 99%
“…57 CD46 is also a clinically "attractive" molecule because single nucleotide polymorphisms in the CD46 gene are either causative or contribute to hemolytic uremic syndrome, age-related macular degeneration, and possibly pre-eclampsia. [58][59][60] On resting CD4 + T cells, CD46 presence sustains (via signals that have not yet been identified) the expression of the interleukin (IL)-7 receptor (CD127). Incoming IL-7R signals in circulating T cells maintain basic glucose transporter 1 (GLUT1) surface expression, which, in turn, allows for glucose-mediated protein kinase B (AKT) activation and anti-apoptotic B cell lymphoma (BCL-2) expression, all such events being required for normal T cell survival in the periphery.…”
Section: The Complosome In T Cell Homeostasismentioning
confidence: 99%
“…The role of the complement system in the pathogenesis of AMD has been studied and reviewed extensively over the past decade (Warwick et al, ; Bora et al, ; McHarg et al, ). Key facts supporting the role of the complement system in the pathogenesis of AMD include the following: (i) Several complement components have been detected in drusen and AMD lesions (Anderson et al, , ); (ii) higher plasma levels of C3a, C3d, Bb, and C5a have been observed in AMD patients (Scholl et al, ; Reynolds et al, ; Lechner et al, ); (iii) polymorphisms in a number of complement genes (CFH, CFB, C2, SERPING1, and C3) are genetic risk factors of AMD (Edwards, ; Cipriani et al, ); and (iv) inhibition of complement suppresses laser‐induced CNV in mice (Nozaki et al, ; Bora et al, ; Kim et al, ; Lipo et al, ). Mechanistically, CFH may inhibit CD47‐mediated resolution of subretinal inflammation and this inhibitory effect could be enhanced by the AMD associated CFH (H402) variant (Calippe et al, ).…”
Section: Targeting the Complement System In Retinal Degenerative Disementioning
confidence: 99%
“…This finding suggests that RPE cells exposed to oxidative insult are permissive for complement activation on their surfaces. A recent case-control studies has reported an absence of an association between AMD and gene variants in CD46, CD55 and CD59 (Cipriani et al, 2012). …”
Section: Complement Components In Rpe-bruch’s Membrane–choroid Commentioning
confidence: 99%